Disaggregated Nano-Hydroxyapatite (DnHAP) with Inhibitory Effects on Biofilms and Demineralization. (July 2023) - Huang, Y.; Han, Q.; Peng, X.; Ren, B.; Li, J.; Zhou, X.; Li, M.; Cheng, L.
Nano-hydroxyapatite (nHAP) is considered a biocompatible agent that promotes the remineralization of dental hard tissue; however, its antibacterial efficacy is under scientific discussion. Therefore, this investigation aimed to specify the inhibitory effects of disaggregated nano-hydroxyapatite (DnHAP) on regrown biofilms and demineralization. Regrown biofilm models of single-species ( Streptococcus mutans ), dual-species ( S. mutans and Candida albicans ), and saliva-derived microcosm biofilms were established in vitro. Repeat treatment with DnHAP was applied to biofilms. The viability, lactic acid, biofilm structure, biomass, the inhibitory effect of demineralization, and virulence factors' expression were determined. In addition, the biofilm microbial community was analyzed by 16S ribosomal RNA gene sequencing. DnHAP inhibited metabolism, lactic acid production, biomass, and water-insoluble polysaccharide production ( P < 0.05) of regrown single/dual-species biofilms. Concerning the saliva-derived biofilms, samples treated with DnHAP showed lower biofilm metabolic activity without significant differences from samples treated with sterile deionized water ( P > 0.05); in addition, saliva-derived biofilms treated with DnHAP exhibited lower lactic acid production ( P < 0.05). The demineralization of bovine enamel was the lowest in the DnHAP group, as detected by transverse microradiography, and the lesion depth and volume decreased significantly ( P < 0.05). The application of DnHAP did not change the diversity of regrown saliva-derived microcosm biofilms. In conclusion, this investigation showed that DnHAP could be a promising solution for the management of regrown biofilms to combat dental caries.